Human rights protection through public interest litigation in India - Singh, Parmanand (1999)
Mainly focusing on raising core human rights issues through PIL, the author, with a brief conceptualisation, traces evolution of PIL in India describing its essential features. He then, discussing contributions of PIL, takes up the areas where police and other governmental agencies indulged freely in deeds of lawlessness and repression in the past but have now been covered effectively by PIL for redressal. In the next section, he discusses the performance of National Human Rights Commission since its inception in 1993 with necessary details on its composition, functions, powers, procedure and role, listing details of action taken by NHRC in 20 important cases. - Reproduced
Keywords: Citizen suits - India; Human rights - India; Human rights